Pendidikan Karakter dalam Islam: Analisis Filosofis Ibnu Miskawaih dalam Kitab Tahzibul Akhlak - Atika Rofiqatul Maula (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
Character education aims to direct students who have good morals. The human existence character mostly comes from the environment, such as innate, culture, and education received. Because the human character is always changed, the path is taken through the educational process, namely upbringing, and training. On the way, the student characters can experience a decrease and even deviations in space. This condition can be influenced by the environment around them. This study aims to find out how the concept of character education according to the Islamic figure, namely Ibnu Miskawaih through his book entitled